#### Answer

See the picture below.

#### Work Step by Step

By calculating the values of $f(x)=\frac{1}{2}x^3-4$ (with blue) and $g(x)=x^3$ (with red) we can see that the following equation is true: $\frac{1}{2}g(x)-4=f(x)$
In order to graph the parent function , here is the table of values:
$f(-2)=-2^3=-8$
$f(-1)=-1^3=-1$
$f(0)=0^3=0$
$f(1)=1^3=1$
$f(2)=2^3=8$
Therefore the graph of $f(x)$ is exactly the same as the graph of $g(x)=x^3$ but is wider (is shrinked vertically by a factor of 2) and is translated 4 units down.